2015
DOI: 10.1039/c5cc03139g
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly formation of a healable lanthanide luminescent supramolecular metallogel from 2,6-bis(1,2,3-triazol-4-yl)pyridine (btp) ligands

Abstract: The synthesis of five new 2,6-bis(1,2,3-triazol-4-yl)pyridine (btp) ligands is described: the self-assembly behaviour of the tri-methyl ester, 1, with Eu(III) showed the formation of a luminescent 1:3 Eu : btp complex, Eu13, which was studied in solution and in the solid state; while the tri-carboxylic acid, 2, formed a hydrogel and its corresponding complex Eu23, gave rise to a strongly red luminescent healable metallogel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 58 publications
1
38
0
1
Order By: Relevance
“…Various types of ligands such as 1,2,3‐triazoles, 2,6‐bis(1,2,3‐triazol‐4‐yl)‐pyridine, 2,6‐bis(1'‐methylbenzimidazolyl)pyridine, terpyridine, and polyethylenimine have been used to prepare gels with transition metal ions or/and lanthanide ions . Compared to other ligands, considerable progress has been made with 2,6‐bis(1,2,3‐triazol‐4‐yl)‐pyridine (btp) units on account of its facile synthesis, versatile modification, and wide scope of coordination with metal ions . The 1,2,3‐triazole and pyridyl rings of btp unit offer nitrogen‐based associating sites for a variety of d and f metal ions .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of ligands such as 1,2,3‐triazoles, 2,6‐bis(1,2,3‐triazol‐4‐yl)‐pyridine, 2,6‐bis(1'‐methylbenzimidazolyl)pyridine, terpyridine, and polyethylenimine have been used to prepare gels with transition metal ions or/and lanthanide ions . Compared to other ligands, considerable progress has been made with 2,6‐bis(1,2,3‐triazol‐4‐yl)‐pyridine (btp) units on account of its facile synthesis, versatile modification, and wide scope of coordination with metal ions . The 1,2,3‐triazole and pyridyl rings of btp unit offer nitrogen‐based associating sites for a variety of d and f metal ions .…”
Section: Methodsmentioning
confidence: 99%
“…When the btp units were incorporated into polymers and then coordinated with transition metal ions, some unique reversible or irreversible properties have been accessed. For example, when the btp motifs were bound with Eu 3+ or Ru 3+ , the resulting complex were used for catalysis and luminescent devices . So far, a range of btp‐containing polymeric complexes with different architectures, for example, linear, star‐shaped, dendritic, and even cylinder motifs, have been prepared .…”
Section: Methodsmentioning
confidence: 99%
“…The value of G′ decreased sharply beyond the linear viscoelastic region, indicating that the system turned into a liquid-like sample. 40,41 Moreover, the experimental results indicated that the mechanical properties of the three-dimensional networks increased together with the increasing cross-linking density and that the yield strain depended on the OG content.…”
Section: Rheological Studies Of the Hydrogelsmentioning
confidence: 96%
“…The role of btzpy in sensitising the emission is eloquently confirmed through excitation spectra, the profiles of which match the ligand-based features observed in electronic absorption spectra. [165] Emissive btzpy-containing Ln(III) complexes have lent themselves to numerous practical applications such as templating agents for 'star-branched' polymers, [166] components within self-assembling healable metallogels [167] or for bioimaging [168], the latter facilitated by their long emission lifetimes, large Stokes shift and the scope for incorporation of biologically relevant substrates at the triazole moiety through 'click' chemistry. Fletcher and co-workers carried out preliminary cellular imaging studies with complexes of the form [Ln(btzpy Bn )3] 3+ where Ln = Eu(III), Tb(III), Dy(III), Sm(III).…”
Section: Lanthanide Complexesmentioning
confidence: 99%